Expectation And Effectiveness Of The Halal Slaughtering Training Towards Employability Among Blue Collar Workers - Norhayati Rafida Abdul Rahim; Alina Abdul Rahim; A. Siti Mashitoh; N.H. Nurul Husna (IDOSI Publications, 2024)
Middle-East Journal of Scientific Research 13 (Approaches of Halal and Thoyyib for Society, Wellness and Health): 11-16, 2013